2020
DOI: 10.3390/languages5020018
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Effect of Spanish Immersion Education on the Acquisition of Pronominal Subjects in Child Heritage Speakers

Abstract: Studies have found that aspects of grammar that lie at the syntax–pragmatics interface, such as the use of pronominal subjects in null-subject languages, are likely to undergo cross-linguistic influence in bilingual speakers. This study contributes to our understanding of the role of Spanish immersion academic instruction on the comprehension of null subjects in English-dominant, Spanish-heritage children living in the United States. Two groups of bilingual children aged 4 to 7 (those attending a Spanish immer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…We hypothesize that we will see evidence of cross-linguistic influence both from Spanish to English and from English to Spanish in the distribution of null and overt subjects, as has been shown to occur in previous studies (Austin et al, 2017;Goldin, 2020aGoldin, , 2020b. We also hypothesize that this influence correlates with language dominance, such that Spanish-dominant children will accept null subjects in continuous contexts in English.…”
Section: 1mentioning
confidence: 56%
See 3 more Smart Citations
“…We hypothesize that we will see evidence of cross-linguistic influence both from Spanish to English and from English to Spanish in the distribution of null and overt subjects, as has been shown to occur in previous studies (Austin et al, 2017;Goldin, 2020aGoldin, , 2020b. We also hypothesize that this influence correlates with language dominance, such that Spanish-dominant children will accept null subjects in continuous contexts in English.…”
Section: 1mentioning
confidence: 56%
“…These findings suggest a complex picture of the development of morphosyntactic and pragmatic abilities. This analysis is surprising given the findings from Shin and Cairns (2012) and Goldin (2020aGoldin ( , 2020b, who found that morphosyntactic abilities develop concurrently with early pragmatic abilities in bilingual and monolingual children until age 5-6, followed by many years of fine-tuning of pragmatic knowledge. The results of our study suggest that it is possible for children to develop morphosyntactic competence and gradually develop pragmatic abilities that mirror those of heritage bilingual adults in their environment.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This model has been tested extensively in studies examining the acquisition of various morphosyntactic features (Hur et al, 2020; Putnam and Schwarz, 2014; Yager et al, 2015, Yager, 2016, amongst others). For instance, previous studies testing this model have used patterns of heritage language use as a proxy for heritage language activation when examining the acquisition of mood selection (Perez-Cortes, 2016), gender selection, and phrasal word order (Cuza and Pérez-Tattam, 2015; Hur et al, 2020), and subject pronoun expression (Goldin, 2020).…”
Section: Accusative Clitics In Spanish and Object Pronouns In Brazili...mentioning
confidence: 99%